STUDENTS QUILOMBOLA: SCHOOL AND ETHNIC IDENTITIES-RACIAL - Sandra Pereira Tosta; Ligia Marise Costa (Editora da Universidade de Santa Cruz do Sul, 2013)
In this article, we consider about the identity construction of young high school students, community residents remaining Quilombo and the contribution of the school for the construction of such identities. We understand that identities are forged, built or denied within different times and places and always in opposition or contrast to other identities, in a game relational or non-recognition of otherness. Among the results, we emphasize that the school is silent on crop Maroons. In contrast to this reality, students listened value school and education as a necessary means to achieve economic rise and somehow contribute to the progress of the community where they live. Finally, we note that such subjects, despite studying outside their community and a school that does not value their culture, yet they recognize and are proud of the condition of being maroon.